Four types of Bifidobacteria trigger autophagy response in intestinal epithelial cells. Issue 11 (November 2014) - Lin, Rong; Jiang, Ye; Zhao, Xin Yan; Guan, Yang; Qian, Wei; Fu, Xiao Chao; Ren, Hun Yu; Hou, Xiao Hua
<x xml:space="preserve">Abstract</x> Objectives To investigate the influence of gut microbiota on autophagy activation in intestinal epithelial cells (IEC) and to evaluate the IEC autophagy response to different types of Bifidobacteria. Methods IEC‐18 cells were treated with lipopolysaccharide (LPS) derived from enteropathogenic Escherichia coli (EPEC) O127:B8 and culture medium supernatants of four types of Bifidobacteria. Transepithelial electrical resistance (TEER) was measured using an epithelial voltohmmeter. Autophagy was determined by transmission electron microscopy (TEM), the ratio of LC3‐II to LC3‐I and the persistence of both green fluorescent protein (GFP) and mCherry signals using a tandem mCherry‐GFP‐LC3 construct. The expression of Atg12–Atg5–Atg16 complex was measured by quantitative real‐time polymerase chain reaction. Results EPEC‐LPS significantly diminished the TEER of IEC compared with untreated controls by 45–55%. This reduction was not observed after treated with Bifidobacteria at all time points. Bifidobacteria could initiate the activation of autophagy in IEC, based on both the ratio of LC3‐II to LC3‐I and TEM. There was no difference in the influence of the four types of Bifidobacteria on the autophagy response. Compared with Bifidobacteria, IEC reacted to EPEC‐LPS much more intensively by autophagy accumulation. More mCherry+LC3 autophagic puncta and increased expressions of autophagy genes Atg5, Atg12 and Atg16 could be detected after being treated with Bifidobacteria and EPEC‐LPS. Conclusions Bifidobacteria initiate autophagy activation in IEC. The Atg12–Atg5–Atg16 multimeric complex might participate in the activation of Bifidobacteria‐induced cell autophagy.